ANALYSIS OF DIFFERENCES IN THE PERCEPTIONS OF ACCOUNTING ACADEMICS REGARDING THE IMPLEMENTATION OF ISLAMIC ACCOUNTING COURSES (CASE STUDY AT MUHAMMADIYAH UNIVERSITY SURABAYA) - Maharani, Rieska; Nuraini, Fitri; A, Andrianto (Universitas Airlangga, 2017)
This study aims to determine differences in perceptions of academics of accounting on the application of sharia accounting courses at the University of Muhammadiyah Surabaya. The object of this study is the perception of accounting academics on the application of sharia accounting subjects with the sampling technique is purposive sampling. The method used deskrip qualitative research by distributing questionnaires and interviews. Results are used to deploy as many as 7 lectures and 21 accounting students who took thesis. Based on the results of questionnaires and interviews can be concluded that there are no differences in the perception of accounting academics of sharia accounting courses at the University of Muhammadiyah Surabaya. And both parties agree will demonstrate the application of sharia accounting subjects, with the course is expected to prospective accountant can apply. Keywords: Perception, Islamic Accounting